KEDUDUKAN END-USER LICENSE AGREEMENT (EULA) DALAM PERLINDUNGAN HAK CIPTA FONT - Asrofi, Muchtar Hasan (JIPRO: Journal of Intellectual Property, 2025)
Abstract. Legal protection is not just about statutory protection to the legal rights of the legal subjects, but also including other sources of law such as agreements. Agreements provide regulations for the parties in a legal relationship and binding them like a law. The End-User License Agreement (EULA) is an example of a written standard license agreement, considering that the clauses/ provisions within it are generally determined by the licensor only. At the same time, EULA seeks to protect certain legal rights, namely copyright of the Font owned by the creator/ licensor. That raises the paradigm of whether the EULA accommodates the interests of the licensee/ Font user and whether it fullfils the aspect of the consensus. This study aims to describe the position of the EULA in the protection of Font copyright through Font creator’s website (digital platform). This study is normative research using conceptual and statute approach. The results of this study are that the EULA positions as a self-regulation; as a form of preventive legal protection; as a law between the parties; and as a permit from copyright holder to recipient of the economic rights of the Font work.   Keywords : Position, EULA, Protection, Copyright   Abstrak. Perlindungan hukum tidak sebatas pada perlindungan dari undang-undang terhadap hak hukum dari subjek hukum, namun juga dari sumber hukum yang lain seperti perjanjian. Perjanjian memberi pengaturan bagi para pihak dalam hubungan hukum dan mengikat selayaknya undang-undang bagi para pihak. End-User License Agreement (EULA) adalah contoh perjanjian lisensi tertulis yang bersifat baku mengingat klausul/ ketentuan di dalamnya umumnya ditentukan sepihak oleh pemberi lisensi, sementara ada hak hukum yang berusaha dilindungi EULA yakni Hak Cipta atas Font milik kreator/ pemberi lisensi. Hal itu seringkali menimbulkan paradigma bahwa apakah EULA mengakomodir kepentingan penerima lisensi ataupun apakah EULA memenuhi unsur kesepakatan. Penelitian ini bertujuan mendeskripsikan tentang kedudukan EULA dalam perlindungan Hak Cipta atas Font di website milik kreator Font. Penelitian ini merupakan penelitian normatif dengan pendekatan konseptual dan perundang-undangan. Hasil penelitian ini ialah EULA bekedudukan sebagai self-regulation; sebagai bentuk perlindungan hukum preventif; sebagai undang-undang bagi para pihak; dan sebagai izin dari pemegang Hak Cipta kepada penerima hak ekonomi atas karya Font.